COMS, the New Eyes in the Sky for Geostationary Remote Sensing - Kim, Han-Dol; Kang, Gm-Sil; Lee, Do-Kyung; Jin, Kyoung-Wook; Seo, Seok-Bae; Oh, Hyun-Jong; Ryu, Joo-Hyung; Lambert, Herve; Laine, Ivan; Meyer, Philippe; Coste, Pierre; Duquesne, Jean-Louis (IntechOpen, 2012)
None